Manajemen Pengembangan SDM Berbasis Coaching dan Mentoring untuk Meningkatkan Efikasi Diri Guru di SMKN 1 Slahung - Fatma, Hawinda Widya; Sulton, Sulton (Universitas Muhammadiyah Ponorogo, 2026)
The paradigm shift in teacher professional development emphasizes the need for continuous, contextual, and job-embedded approaches. This study aims to analyze human resource development management based on coaching and mentoring to enhance teachers’ self-efficacy at State Vocational High School 1 Slahung. A systematic-conceptual literature review was employed to synthesize empirical and theoretical studies on teacher professional development, self-efficacy, and the implementation of coaching and mentoring in educational settings. The findings indicate that coaching and mentoring, when strategically integrated into school human resource management systems, have a positive and significant impact on teachers’ self-efficacy across pedagogical, classroom management, and professional engagement dimensions. Coaching primarily strengthens teachers’ confidence through reflective feedback and mastery experiences, while mentoring supports psychosocial development and professional identity formation. The study concludes that integrated coaching and mentoring-based human resource development management constitutes an effective and sustainable strategy for enhancing vocational teachers’ self-efficacy. This approach positions professional development not as a fragmented activity but as a core component of school management and teacher empowerment.